Model Meaningful Learning untuk Meningkatkan Kreativitas Pada Pembelajaran Menulis Cerita - Mulyani, Ani Sri; Yudiyanto, Mohamad; Sabirin, Ayuni (Jurnal Ilmiah Wahana Pendidikan, 2023)
Creativity in learning is not just about producing artistic works, but also about developing the critical thinking, problem-solving, and adaptability necessary to succeed in an ever-changing world. This study aims to analyze the meaningfull learning model in increasing students' creativity in writing stories. The research method used is library research. The results show, the meaningful learning model provides a strong foundation to increase student creativity in learning to write stories by providing a deep, relevant, and motivating learning environment. By integrating the principles of this model into learning practices, teachers can provide more meaningful and fulfilling learning experiences for students, while stimulating their continued development of creativity.